Economic assessment of heat and power generation from small-scale liquefied natural gas in Russia - Pavel Tcvetkov; Alexey Cherepovitsyn; Alexey Makhovikov (Energy Reports, 2020)
Small-scale production of liquefied natural gas (SS LNG) is a promising, but little-known direction of the gas industry development, which is aimed at meeting the needs for environmentally friendly decentralized energy supply of nearby regions. In this study, an economic efficiency of four energy generation options, based on SS LNG, with nominal capacities from 0.3 to 3 MW was assessed. Total cost of heat and electricity at different delivery distances was determined. A number of regression models were developed to determine the key technical and economic characteristics of energy plants. The results showed that only 9 out of 85 Russian regions have sufficiently high tariffs for heat and electricity for effective SS LNG energy generation. It was also found that the average cost increase depending of delivery distance is 1.23 %/km for electricity and 2.51 %/km for heat.
Keywords: 330; Economic efficiency; Energy tariffs; Heat and power generation; Russian regions; Small-scale LNG